Composite Resin Preheating Techniques for Cementation of Indirect Restorations - Lousan do Nascimento Poubel, Déborah; Ghanem Zanon, Ana Elisa; Franco Almeida, Júlio César; Vicente Melo de Lucas Rezende, Liliana; Pimentel Garcia, Fernanda Cristina (International Journal of Biomaterials, 2022)
Purpose. Resin-based materials have been preheated by using different techniques and commercial devices. However, a consensus on the clinical protocol for cementing with preheated composite resins is lacking. The aim of this scoping review was to identify the different methods used for heating composite resins as used for cementing indirect adhesive restorations and to determine the benefits and limitations. Study Selection. A search was performed on PubMed/MEDLINE, Embase, Cochrane, Web of Science, Scopus, LIVIVO, and the nonpeer-reviewed literature database. Studies on preheating composite resins for cementing indirect restorations were included, with no restrictions on the type of study, year of publication, or language. The following data were extracted: preheating technique, the device used for preheating, preset temperature, and warming time. Results. In total, 304 studies were identified. After removing duplicates, 270 articles were selected, and 14 articles were included in the final evaluation. Half of the included studies reported similar preheating techniques using the Calset device for composite resins. The temperatures of 54°C and 68°C were most frequently reported, with a mean warming time of 5 minutes. Conclusions. Preheating composite resins for the cementation of indirect restorations reduces viscosity, but the material must be used promptly after removal from the device. Practical Implications. Different methodologies for preheating composite resins have been reported and used in clinical dental practice. To achieve good results and guide the clinician on use, the techniques for heating composite resins for cementation need to be standardized. Keeping the material warm until the restorative procedure, the thickness of the indirect restoration, and the composition of the composite resins can directly affect the outcome of the procedure.